Seed Dormancy and Germination 2020
DOI: 10.5772/intechopen.86833
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death in Seeds: An Adaptive Mechanism Required for Life

Abstract: The regeneration of the mother plant through germinative process is the main reason that evolutionarily justifies the existence of a viable seed. Current knowledge indicates that the control of germination is a sophisticated process mainly controlled by hormones and reactive oxygen species (ROS), among other endogenous factors. One of the events that directly participate in the germination is the degradation of storage proteins (SPs). Thus, vacuolar processing enzymes (VPEs) contribute to SPs' degradation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 124 publications
0
10
0
1
Order By: Relevance
“…Ning et al (2002) suggested that this pattern of DNA fragmentation may be a universal marker of nuclear change during plant programmed cell death. This systematic DNA fragmentation was associated with significant increase in nucleases activity (Sakamoto and Takami 2014;Matilla 2020). Langston et al (2005) who stated that the nucleic acid catabolism must be catalysed by endonucleases enzymes which are having task of digesting both single-stranded DNA (ssDNA) and double stranded DNA (dsDNA).…”
Section: Discussionmentioning
confidence: 99%
“…Ning et al (2002) suggested that this pattern of DNA fragmentation may be a universal marker of nuclear change during plant programmed cell death. This systematic DNA fragmentation was associated with significant increase in nucleases activity (Sakamoto and Takami 2014;Matilla 2020). Langston et al (2005) who stated that the nucleic acid catabolism must be catalysed by endonucleases enzymes which are having task of digesting both single-stranded DNA (ssDNA) and double stranded DNA (dsDNA).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Hibiscus surattensis L., these aborted seeds were found in the same plant as well as plants growing in different localities. Such occurrence indirectly implies that apart from the external factors, genetic factor in scripted in the genes operate the programmed cell death in the maturing seeds at one point of time during the seed maturation and/or hormonal regulations controlled by specific genes (Matilla, 2019;Ozga, Kaur, Savada, & Reinecke, 2016;Wiens, King, Nickrent, Calvin, & Vivrette, 1989). In such cases, it could reasonably be presumed that abortive seed production might also be a genetic character and this character can be considered as species specific in Hibiscus surattensis L. However, to elucidate such presumption, further study is required to trace out at what stage and what genetic cue is responsible for such abortion during seed maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Bitkilerde Programlı Hücre Ölümü moleküler mekanizmalar tarafından organize edilmektedir (Locato ve De Gara, 2018;Balakireva ve Zamyatnin, 2019;Matilla, 2019).…”
Section: (3): 1700-1712 2021unclassified